Crossroads: A Framework for Developing Proximity-based Social Interactions - Liang, Chieh-Jan Mike; Jin, Haozhun; Yang, Yang; Zhang, Li Lyna; Zhao, Feng (Mobiquitous (International Conference on Mobile and Ubiquitous Systems: Computing, Networking and Services), 2013)
Proximity-based Social Interaction (PSI) apps are emerging on mobile platforms. While both industries and academic communities have developed frameworks to simplify the PSI app development, our framework, Crossroads, brings a set of features to balance the development overhead and developer expressiveness. We argue that APIs with application hints give developers the expressiveness, and core services (such as virtual links over the star topology) simplify network maintenance. Finally, PSI-specific primitives (such as presence beaconing with interval decaying and group dissemination) improve the energy efficiency. Evaluation results on real smartphones show the energy efficiency gain, topology robustness, and lower group dissemination load.